An Examination of Marketing Strategies on Financial Performance within the Context of the Fertilizer Industry in Malaysia: A Conceptual Framework - Lai, Fong Woon (2012)
In recent years there has been a growing emphasis on strategies in marketing in terms of market positioning, brand equity issues, service quality, market segmentation, competitive differentiation, market structure, market expansion, market pattern and so on. This paper presents a conceptual framework for examining the effect of marketing strategy on financial performance within the fertilizer industry in Malaysia. Accounting, market, and risk adjusted performance measures are employed to gauge the financial performance. The framework espoused in this paper will provide insights into the various marketing strategies necessary for a successful introduction of new products in the fertilizer industry. The proposed framework has theoretical significance in filling the gap of the body of knowledge in the implementation of marketing strategy in the Malaysian fertilizer industry. This paper discusses issues in relation to the role of marketing strategy which have profound impact on organizational financial performance.